The Role of Dikmas and Dikyasa Units in Reducing the Number of Traffic Accidents in the Tasikmalaya Police Legal Area (Indonesian Journal of Police Studies, 2024)
The development of transportation is increasingly increasing, especially land transportation. Every development will definitely arise a problem, with the development of transportation arises the problems that occur on the highway, such as traffic jams, traffic violations and accidents. Accidents themselves can cause casualties both victims suffered minor injuries, severe to death. In Indonesia alone the incidence of accidents continues to increase as well as accidents in the area of Tasikmalaya Regency increasing from 2017 to 2019. The Dikyasa Unit conducts the Dikmas Lantas activities provided to the community. This study aims to explain the general picture of accidents that occur, the implementation of Dikmas Lantas activities carried out, supporting and inhibiting factors in the implementation of Dikmas Lantas activities. This research uses a qualitative approach with field research techniques. The location of the study was at the Tasikmalaya Regional Police Resort with a focus on implementing the community education program. Using data triangulation there are 4 kinds of techniques, namely sources, theories and techniques as well as primary, secondary data sources. Data validity is data reduction, data display. This study uses management theory, communication theory, role theory and the concept of community education and then the concept of traffic accidents. The implementation of community health activities is then due to human factors and road factors. The implementation of the community health program then is already running but not yet maximally. The inhibiting factors are lack of personnel, lack of quality personnel, lack of public awareness, lack of advice and community enthusiasm. the supporting factor is that it has cooperated with government agencies and traffic rules into PKN lessons. The conclusion is that the Police Precinct Unit must increase the number of personnel, train communication skills and include personnel for vocational education, completing the lack of facilities.
Keywords: tes